2014
DOI: 10.5430/jnep.v4n5p29
|View full text |Cite
|
Sign up to set email alerts
|

Using simulation to assess undergraduate nursing students’ competency with medication administration to a limited- English language proficiency patient

Abstract: Background/Objectives: Medication errors continue to be an area of concern in health care and are a significant cause of morbidity and mortality in both inpatient and outpatient settings. Little consideration has been given to the role of the patient in the medication process; patients with limited-English language proficiency (LEP) may be at risk for medical errors and drug complications. The purpose of this research study is to assess undergraduate nursing students' competency with medication administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…34 In this regard, holding a workshop on pharmaceutical calculations has been accompanied by increasing the skills of nurses in pharmaceutical calculations. 35 Implementing a drug dose calculation training program is recommended for nursing students, which can diminish mathematical anxiety, ameliorate drug dose calculations, and ultimately improve patient safety. 16 Ullah et al 27 showed a 39.86% difference in the rate of…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 In this regard, holding a workshop on pharmaceutical calculations has been accompanied by increasing the skills of nurses in pharmaceutical calculations. 35 Implementing a drug dose calculation training program is recommended for nursing students, which can diminish mathematical anxiety, ameliorate drug dose calculations, and ultimately improve patient safety. 16 Ullah et al 27 showed a 39.86% difference in the rate of…”
Section: Discussionmentioning
confidence: 99%
“…Dimensional analysis has been mentioned as a suitable approach to foster the qualification of students' mathematics in the first-year students of chemistry 34. In this regard, holding a workshop on pharmaceutical calculations has been accompanied by increasing the skills of nurses in pharmaceutical calculations 35. Implementing a drug dose calculation training program is recommended for nursing students, which can diminish mathematical anxiety, ameliorate drug dose calculations, and ultimately improve patient safety 16.…”
Section: Discussionmentioning
confidence: 99%